The Philanthropy Scale: a Sociological Perspective in Measuring New Forms of Pro Social Behaviour - Theo Schuyt; Rene Bekkers; Jan Smit (Social Work & Society, 2011)
In wealthy countries, philanthropy is conspicuous back on stage. It appears in new forms, worldwide. As a result, scholarly attention for philanthropy is growing. Philanthropic goals refer to persons, groups and communities who, in most cases, are not personally known to the giver. In research, however, philanthropic motivations of individuals are usually measured by socio-psychological scales which presuppose direct interactions. Measuring philanthropy could therefore be improved by incorporating a sociological frame of reference as well. As a starting point, this article presents a preliminary version of the philanthropy scale that has been tested in the panel survey of the Giving in the Netherlands (GIN) study. The results are discussed in terms of shortcomings and challenges for further research.